Mitigating moral distress by enhancing healthcare workers’ understanding of challenges faced by carers of children with disabilities in low-resource settings in Kenya - Anne Geniets; Jarim Omogi; Laura Hakimi; Alice Lakati; Niall Winters (Global Health Action)
Background Little is known about the psychological wellbeing and the potential moral distress faced by female carers of children with disabilities living in low-resource settings in East Africa. In such environments, caregiving often requires resilience and resourcefulness, yet can also increase the vulnerability of caregivers and their children. Objective The objective of this study is to identify factors affecting female caregivers’ psychological well-being, and to suggest ways healthcare workers can support these caregivers’ psychological well-being to alleviate moral distress. Methods Employing an intersectional convergent parallel mixed-methods approach, the research explores the factors affecting the psychological wellbeing of caregivers in one urban and one rural low-resource setting in Kenya. Results The study identifies strengthening and inhibiting factors, across three dimensions, that moderate caregivers’ experiences of moral distress, and puts forward suggestions for healthcare workers on how to support caregivers’ psychological wellbeing. Conclusions Female carers of children with disabilities in low-resource settings in Kenya face numerous psychological, social and systemic challenges which jeopardize their caregiving, leading to moral distress. Paediatricians and nurses can contribute to enhance the caregivers’ coping-strategies and psychological well-being through simple changes, like explaining a child’s condition in non-technical language. Community health workers can help strengthen the caregivers’ already existing resources by accompanying them in the day-to-day care of their children and by helping them establish self-support groups. Consequently, improved training of healthcare- and community health workers in the field of childhood disability is needed to strengthen health systems, and to support these caregivers and their children.